Dengue Fever Epidemiological Investigation In The District Rawalpindi, Punjab, Pakistan (Journal of Pharmaceutical Negative Results, 2023)
The mosquito-borne virus that causes dengue fever has emerged as a major public health problem in recent decades. Dengue fever prevalence in District Rawalpindi was investigated in this study, between August to October, 2022. About 160 blood samples were taken from patients at the Islamabad Medical Lab (Rawalpindi, Punjab) who were suspected of having dengue fever based on their symptoms. Dengue IgM, IgG, and NS1 (Nonstructural protein antigen of virus) serology tests were carried out. About 116 males and 44 females were found to have contracted dengue fever. The 21-30 age group was the largest single demographic, 78 people from Rawalpindi, 47 people from Taxila and 35 people from Kahuta were the worst hit in the district Rawalpindi. As a result, the health department needs to take charge and start spreading awareness about the importance of keeping public spaces clean. Efforts to combat diseases and infections spread by vectors should actively involve the local populace.